Time-Varying Correlation Between Stock and Government Bond in Asia: Flight-to-Quality - Margani, Mahanani; Husodo, Zaafri Ananto (Jurnal Politik Indonesia: Indonesian Political Science Review, 2022)
This study aims to provide an overview of how the relationship between stock and bond market in Asia when a crisis occurs (in this case the 2008 global crisis and the COVID-19 pandemic) using the DCC-GARCH method to prove the flight-to-quality phenomenon in Asia (China, Japan, Indonesia, Singapore, Malaysia, Thailand, and India). The results showed that during the 2008 global crisis, the flight-to-quality phenomenon happened in Thailand where the correlation between stock returns and government bonds in that country became increasingly negative during the crisis period, indicating that there was a shift in investment from stocks to government bonds. In addition, this research also proved that during the COVID-19 pandemic, the flight-to-quality phenomenon was also proven to occur in Malaysia.